Impact of additional guidance in science education on primary students’ conceptual understanding - Decristan, Jasmin; Hertel, Silke (The Journal of educational research, 2015)
A cognitive and a guidance dimension can describe the support of students’ conceptual understanding in inquiry-based science education. The role of guidance for student learning has been intensively discussed. Furthermore, inquiry learning may pose particular challenges to students with low language proficiency. The present intervention in primary school (54 teachers, 1,070 students) aimed to examine the effects of additional guidance. Therefore, the control group uses a science unit mainly addressing the cognitive dimension of inquiry. In the 3 treatment groups, this unit was enriched with guidance through scaffolding instructional discourse, formative assessment, or peer-assisted learning. The results (43 teachers, 873 students) confirm that in each intervention condition, students’ conceptual understanding significantly improves. In the formative assessment group, students’ mean conceptual understanding is higher than in the control group. Moreover, formative assessment and scaffolding instructional discourse provided particular support to the conceptual understanding of students with poor language proficiency.
Gesehen am 19.04.2017